EFEKTIVITAS PENERAPAN MODEL CREATIVE PROBLEM SOLVING TERHADAP HASIL BELAJAR SMPN 02 SUNGAI RAYA - Istiawan, Dicky; Sulystiarini, Mashudi; Sulystiarini, Sulystiarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbsractThis study was aimed to determine the effectiveness of applying the creative problem solving learning models with the use of conventional learning models. The form used in this research was quasi experimental with nonequivalent control group design. The tool of data collection in this study was a multiple choice learning result and observation sheet. The results of hypothesis testing using one sample test t test with ? = 5% was obtained Zhitung = 7.454 (Zhitung> Z table), which in the rejection area Ho. This showed that there were significant differences between student learning outcomes which taught by using creative problem solving learning models with those which taught by using conventional models. There was an increase of the mean score after giving the treatment of applying creative problem solving learning models in the experimental class, which the mean score of pre test was 50.16 and the mean score of post test was 87.58. There was also an increase of experimental class in the percentage of completeness which the score of pre test completeness percentage was 09.68% and the score of post-test completeness percentage was 100%. Thus, it can be concluded that the use of creative problem solving learning models in maritime and agricultural economic strengthening subject in Indonesia at the eighth grade of SMP Negeri 02 Sungai Raya showed a very effective criteria for improving student learning outcomes, with a difference percentage was 90.32% and the effect size was 0.98. Keywords: Effectiveness, Creative Problem Solving Models